Notes on Habit Formation and Socially Optimal Growth - Simone Valente (ETH Zurich, CER-ETH - Center of Economic Research, 2006)
The interaction between habit formation and pollution-type ex- ternalities modifies the social optimum through discount effects and elasticity effects. If the substitution elasticity does not exceed unity, both effects reduce optimal consumption and capital in the long run, and the optimal capital-income tax increases with the relative impor- tance of habits. Similar results hold with high elasticity if the relative importance of habits is sufficiently high.
Keywords: D62; D91; E21; 330; externalities; habit formation; pollution; optimal growth; Konsumentenverhalten; Lebenszyklus; Optimales Wachstum; Umweltbelastung; Externer Effekt